2018
DOI: 10.2147/clep.s166309
|View full text |Cite
|
Sign up to set email alerts
|

Selective serotonin reuptake inhibitor use and mortality, postoperative complications, and quality of care in hip fracture patients: a Danish nationwide cohort study

Abstract: PurposeTo examine the association between selective serotonin reuptake inhibitor (SSRI) use and mortality, postoperative complications, and quality of in-hospital care in hip fracture patients.Patients and methodsThe study was a nationwide cohort study based on individual-level linked, prospectively collected data from Danish population-based national registries covering all hospitals in Denmark. The health care system in Denmark is tax-funded, and all citizens have equal access to health care services. We inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Furthermore, patients redeeming 2 prescriptions are more likely to take their medication and a sensitivity analysis in a previous study showed no difference between hip fracture patients redeeming only 1 prescription and those redeeming 2 (Bruun et al. 2018). Second, comorbidity information was obtained from the Danish National Patient Registry, which holds only data on patients treated in the hospital sector.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, patients redeeming 2 prescriptions are more likely to take their medication and a sensitivity analysis in a previous study showed no difference between hip fracture patients redeeming only 1 prescription and those redeeming 2 (Bruun et al. 2018). Second, comorbidity information was obtained from the Danish National Patient Registry, which holds only data on patients treated in the hospital sector.…”
Section: Discussionmentioning
confidence: 98%
“…14,19,21,24,38 The medications used to treat depression are not without risk, as antidepressant medications are a known risk factor for falls and adverse operative outcomes. 3,4,21 This is due to the wide variety of adverse effects associated with antidepressants including but not limited to sedation, orthostatic hypotension, and anticholinergic effects. 37,38 Importantly, antidepressant use is reported by almost 13% of people in the United States illuminating that antidepressant use may be one of the most commonly encountered risk factors for postoperative falls by orthopaedic surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] An association between fulfillment of the process performance measures and better survival and lower readmission rate has been found [25][26][27][28] as well as an association between orthogeriatric specialization or patient volume and outcome. [29][30][31] In addition, associations between transfusion practice and outcome, 32,33 association between surgery delay and post-operative complications, 34,35 associations between some commonly used medication preoperatively, including antidepressants, anticoagulants and anti-inflammatory drugs and post-operative complications [36][37][38][39][40] have been observed. Moreover, studies have found that about 15% of hip fracture patients develop an acute kidney injury within 5 days of surgery 41,42 and about 15% of patients sustain postoperative infections within 30 days of surgery, 43,44 complications which are strongly associated with 30 days mortality.…”
Section: Examples Of Researchmentioning
confidence: 99%